Spectrum of thrombocytopenia: A clinicopathological study with review of the literature - Ekta Paramjit; Rajiv Rao; S Sudhamani; Prakash Roplekar; Zeba Shaffi; Sukriti Roy (Wolters Kluwer Medknow Publications, 2016)
Background: Thrombocytopenia has been defined as a subnormal number of platelets in the circulating blood and may result from four processes: Artifactual thrombocytopenia, deficient production of platelets, accelerated destruction, and abnormal distribution or pooling of the platelets. Aims: To find out the etiology of thrombocytopenia with clinicopathological correlation, to grade it on the basis of platelet count, and to know the age and sex distribution of the cases. Materials and Methods: The study was conducted from January 2015 to June 2015. A total of 300 cases of thrombocytopenia were selected. All the patients with platelet counts less than 150 Χ 10 3 / micro liter (μL), were included. On the basis of platelet count, the cases were divided into the four grades and clinicopathological correlation was done. Statistical Analysis: Simple random sampling, mean, and percentage. Results: The most common cause for thrombocytopenia was infection. Alcoholic liver disease was the most common noninfective cause. Maximum number of patients were in the age group of 20-39 years. The commonest grade of thrombocytopenia was Grade 1, the least common being Grade 4. Conclusion: Thrombocytopenia is usually associated with infections such as malaria, dengue, sepsis, and viral diseases. It is less common in noninfective conditions, for example alcoholic liver disease. It is seen mainly in adults, significantly more in males, and present as Grade I.